Application of electrokinetic remediation on contaminated alluvial soils in Sri Gading, Batu Pahat, - Mohamed Johar, Saffuwan (2020)
The research described in this thesis is a comprehensive account to remove excessive heavy metals and radionuclides contained in the most radiation-contaminated soil by using the most optimised electrokinetic remediation technique. This novel study that saved time and costs based on electrokinetic optimisation was the ultimate vision to be discovered on this thesis. In addition, reduction in terrestrial gamma radiation doserate (TGRD) by reducing soil pH level during electrokinetic processes was somewhat new and exciting in this study. The TGRD and soil pH of various soil type within Batu Pahat and Kluang districts were measured. Soil with the highest TGRD was selected to be remediated by various types of electrokinetics setup, to list out the best electrokinetic parameters. Results obtained from these setup led to the development of the most optimised electrokinetic setup, especially in remediating radionuclides. Data analysis showed that Holyrood-Lunas soil species taken from Sri Gading recorded the highest TGRD of 476.841.9 nGy h-1 . The pre-electrokinetic examination by X-ray fluorescence (XRF) indicated that 10 heavy metals contained in the sample were significantly higher than the Environmental Protection Agency (EPA) contamination indices limit, in decreasing order, were Th>As>Sb>Sn>U>Cr>Pb>Ni> V>Zr. The post-electrokinetic analysis suggested the most optimised parameters for Th and U removals were 3.0 hours remediation time, 30 volts electrode voltage, 22 cm electrode spacing, plate-shaped electrodes by 88 cm and in 1-D electrodes configuration. Applications of these optimised parameters by high-pure germanium (HPGe) analysis gave a very low 232Th and 238U removals at 2.7423.78 and 0.232.64 ppms, respectively, while for the pilot scale electrokinetic setup shows average removals at 1.4793.09 and 0.214.11 ppms, respectively. The relationships between 232Th and 238U concentrations with soil pH changes supported the initial hypotheses that reducing TGRD can be obtained by reducing soil pH level during the electrokinetic remediation process. Thus it can be concluded that the findings of this research can contribute towards the best soil decontamination.